2019
DOI: 10.1002/jbm.a.36615
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of mouse induced pluripotent stem cells using the three‐dimensional culture with ultra‐purified alginate gel

Abstract: As articular cartilages have rarely healed by themselves because of their characteristics of avascularity and low cell density, surgical intervention is ideal for patients with cartilaginous injuries. Because of structural characteristics of the cartilage tissue, a three‐dimensional culture of stem cells in biomaterials is a favorable system on cartilage tissue engineering. Induced pluripotent stem cells (iPSCs) are a new cell source in cartilage tissue engineering for its characteristics of self‐renewal capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…To date, several studies have demonstrated induction of chondrogenic differentiation of mouse iPSCs; however, the induction methods used in previous reports are slow and require a long period of time. For example, Hontani et al 6 reported a method to induce chondrogenic differentiation of mouse iPSCs using 3D culture with an ultra-purified alginate gel, in which iPSCs were first guided to differentiate into MSCs by repeated passaging. Then, the cells were seeded on the alginate scaffold and subjected to chondrogenic differentiation for 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several studies have demonstrated induction of chondrogenic differentiation of mouse iPSCs; however, the induction methods used in previous reports are slow and require a long period of time. For example, Hontani et al 6 reported a method to induce chondrogenic differentiation of mouse iPSCs using 3D culture with an ultra-purified alginate gel, in which iPSCs were first guided to differentiate into MSCs by repeated passaging. Then, the cells were seeded on the alginate scaffold and subjected to chondrogenic differentiation for 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hontani et al . 6 reported a method to induce chondrogenic differentiation of mouse iPSCs using 3D culture with an ultra-purified alginate gel, in which iPSCs were first guided to differentiate into MSCs by repeated passaging. Then, the cells were seeded on the alginate scaffold and subjected to chondrogenic differentiation for 28 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic stem cells seeded on elastic polydimethylsiloxane scaffolds and subjected to mechanical loading resulted in robust induction of chondrogenic differentiation [ 30 ]. Embryonic stem cell application-related ethical issues can be avoided by replacement with iPSCs that were also shown to be effective in chondrogenic ECM production [ 31 ]. However, the difficulties in directing pluripotent stem cells towards specific mature lineages and iPSCs genomic instability often complicates their use in different applications [ 32 ].…”
Section: Tissue Engineering Technologies For Cartilage Regenerationmentioning
confidence: 99%
“…Until today, there have been only a few published attempts at combing biomaterials with iPSCs to promote chondrogenic differentiation. For instance, Hontani et al [ 38 ] came up with a novel chondrogenic differentiation method based on a combination of 3D cultivation in ultra-purified alginate gel as a scaffold and step-wise differentiation of iPSCs into chondrocytes via the MSC-like cell stage. iPSC-MSCs in alginate gel were supplemented with MSC induction medium.…”
Section: Alternative Approaches In Ipsc-based Cartilage Reconstrucmentioning
confidence: 99%